The impact of mental illness on criminal responsibility - Lecturer Dr. Sami Madb Mohamed; Assistant Lecturer Hussein Ahmed Kamal El Din (The college of law and political science journal, 2023)
The impact of mental illness on criminal responsibility           The human brain is the center that drives all body organs and controls all the body's functions. Therefore, since the beginning of studying science, scientists have sought to research and understand the brain and its associated effects on human behaviors. Also, they strived to explore the mysterious secrets of various mental diseases and whether these diseases make people lose consciousness and awareness.In this regard, law philosophers have diverse opinions about the impact of mental diseases and disorders on human free will and behavior—moreover, the effect of that on penal responsibility for mentally ill criminals.Most legal jurisprudence has considered awareness as an essential element of criminal responsibility based on the infliction of punishment. Accordingly, the Iraqi legislator proceeded. Mind...). Research on this topic raises several concerns, such asWhat is the standard in determining criminal responsibility? What is the possibility of linking mental disorders to criminal behavior? And what is the possibility of treating criminal behavior with medical drugs or certain brain surgeries?